Identification of Immune Activation Markers in the Early Onset of COVID-19 Infection - Kovarik, Johannes J.; Kämpf, Anna K.; Gasser, Fabian; Herdina, Anna N.; Breuer, Monika; Kaltenecker, Christopher C.; Wahrmann, Markus; Haindl, Susanne; Mayer, Florian; Traby, Ludwig; Touzeau-Roemer, Veronique; Grabmeier-Pfistershammer, Katharina; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
This study aimed to determine the specific cytokine profile in peripheral blood during the early onset of COVID-19 infection. This was a cross-sectional exploratory, single center study. A total of 55 plasma samples were studied. Serum samples of adults showing symptoms of COVID-19 infection who were tested positive for SARS-COV-2 infection (CoV+, n=18) at the COVID-19 outpatient clinic of the Medical University of Vienna were screened for immune activation markers by Luminex technology. Additionally, age and gender-matched serum samples of patients displaying COVID-19 associated symptoms, but tested negative for SARS-COV-2 (CoV-, n=16) as well as healthy controls (HC, n=21) were analyzed. COVID-19 positive (CoV+) patients showed a specific upregulation of BLC (141; 74-189 pg/mL), SCD30 (273; 207-576 pg/mL), MCP-2 (18; 12-30 pg/mL) and IP-10 (37; 23-96 pg/mL), compared to patients with COVID19-like symptoms but negative PCR test (CoV-), BLC (61; 22-100 pg/mL), SCD30 (161; 120-210 pg/mL), MCP-2 (8; 5-12 pg/mL ) and IP-10 (9; 6-12 pg/mL) and healthy controls (HC) (BLC 22; 11-36 pg/mL, sCD30 74; 39-108 pg/mL, MCP-2 6; 3-9. pg/mL, IP-10 = 8; 5-13). The markers APRIL, sIL-2R, IL7, MIF, MIP-1b, SCF, SDF-1a, sTNF-RII were elevated in both CoV+ and CoV- patient groups compared to healthy controls. HGF, MDC and VEGF-A were elevated in CoV- but not CoV+ compared to healthy controls. BLC, sCD30, MCP-2 and IP-10 are specifically induced during early stages of COVID-19 infection and might constitute attractive targets for early diagnosis and treatment of this disease.